Explicit recognition of emotional facial expressions is shaped by expertise: evidence from professional actors - Conson, Massimiliano; Ponari, Marta; Monteforte, Eva; Ricciato, Giusy; Sarà, Marco; Grossi, Dario; Trojano, Luigi (Frontiers in Psychology, 2013)
Can reading others’ emotional states be shaped by expertise? We assessed processing of emotional facial expressions in professional actors trained either to voluntary activate mimicry to reproduce character’s emotions (as foreseen by the “Mimic Method”), or to infer others’ inner states from reading the emotional context (as foreseen by “Stanislavski Method”). In explicit recognition of facial expressions (Experiment 1), the two experimental groups differed from each other and from a control group with no acting experience: the Mimic group was more accurate, whereas the Stanislavski group was slower. Neither acting experience, instead, influenced implicit processing of emotional faces (Experiment 2). We argue that expertise can selectively influence explicit recognition of others’ facial expressions, depending on the kind of “emotional expertise”. These results demonstrate that not only simulative processes involved in action recognition but also those related to more complex aspects of social cognition (such as emotion recognition) can be affected by expertise.